PENGARUH PEMBERIAN JUS PEPAYA TERHADAP PENINGKATAN KADAR HB PADA IBU HAMIL DENGAN ANEMIA YANG MENDAPATKAN SUPLEMENTASI TABLET FE DI KLINIK PRATAMA RAWAT INAP BUNDA PATIMAH MEDAN - Stefani Anastasia Sitepu (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Anemia that occurs in pregnant women is iron deficiency anemia, the impact of this anemia can cause death for both mother and baby.The purpose of this study was to determine the effect of papaya juice on increasing Hb levels in pregnant women with anemia who received iron tablets supplementation at the Bunda Patimah Inpatient Clinic, Medan. This study used a quasi-experimental design with the Pre and Post Test Control One Group design, namely seeing the difference before and after being given. The population in this study were 10 respondents. In this study using the Paired T Test. The results showed that the average increase in Hb levels of pregnant women with anemia before and after being given papaya juice was 4,300, Std. Deviation 11,374, Std. Error Mean 3,597 with 95% CI = 2.263 - 28,537 with p value = 0.000. The conclusion of this study was that there was an effect of giving papaya juice on increasing Hb levels in pregnant women with anemia who received iron tablets supplementation at the Bunda Patimah Inpatient Clinic, Medan. It is suggested to the Mother Patimah Inpatient Primary Clinic in Medan as a reference for further researchers of about the benefits of giving papaya..